Standardizing Cytological Reporting: The WHO Reporting System of Lymph Node Cytology and its Impact on Clinical Practice - Tasneem, Sabeha; Kairi, Sushmita; Naiding, Momota (Annals of Pathology and Laboratory Medicine, 2025)
Background: Lymphadenopathy commonly results from benign conditions such as reactive hyperplasia or lymphadenitis. Fine needle aspiration cytology (FNAC) is widely used for initial evaluation due to its speed, affordability, and diagnostic utility. To improve consistency, the World Health Organization (WHO) and International Academy of Cytology developed a standardized reporting system for lymph node cytology. In this study, we aim to classify the findings of lymph node cytopathology as per the WHO system and assess the Risk of Malignancy through histopathological correlation. Methods: A retrospective study of 240 cases was conducted at SMCH over one year (July 2023-July 2024). Cases with available histopathology or follow-up data were included. ROM was calculated by correlating cytological diagnoses with final outcomes. Results: Cervical lymphadenopathy was most frequent (82%), with a slight male predominance. Benign lesions comprised 71.25% of cases, mostly reactive lymphadenitis (76%). Malignant cases (17.91%) were predominantly metastatic squamous cell carcinoma (77%). ROM was highest in the suspicious and malignant categories (100%) and lowest in the benign group (2.34%). Conclusion: The WHO Reporting System for Lymph node Cytopathology provided a clear, reproducible framework that improved diagnostic accuracy in our study. High Risk of Malignancy in atypical, suspicious, and malignant categories aligns with previous research, confirming the system's reliability. Low Risk in benign and inadequate categories emphasizes cautious interpretation and follow-up. This standardized approach enhances communication between cytopathologists and clinicians, improving patient management.